Regioselectively modified sulfated cellulose as prospective drug for treatment of malaria tropica - Schwartz-Albiez, Reinhard; Adams, Yvonne; von der Lieth, Claus-W.; Mischnick, Petra; Andrews, Katherine T.; Kirschfink, Michael (Glycoconjugate journal, 2007)
Adhesion of Plasmodium falciparum infected erythrocytes (IE) to placental chondroitin-4-sulfate (CSA) has been linked to the severe disease outcome of pregnancy-associated malaria. Consequently, sulfated polysaccharides with inhibitory capacity may be considered for therapeutic strategies as anti-adhesive drugs. During in vitro screening a regioselectively modified cellulose sulfate (CS10) was selected as prime candidate for further investigations because it was able to inhibit adhesion to CSA expressed on CHO cells and placental tissue, to de-adhere already bound infected erythrocytes, and to bind to infected erythrocytes. Similar to the undersulfated placental CSA preferred by placental-binding infected erythrocytes, CS10 is characterized by a clustered sulfate pattern along the polymer chain. In further evaluation of its effects on P. falciparum interactions with host erythrocytes, we now show that CS10 inhibits the in vitro asexual growth of parasites in erythrocytes. Furthermore, we show that CS10 interferes with C1 of the classical complement pathway but not with MBL of the lectin pathway. In order to gain insights into the possible interactions of CS10 with known parasite receptors at the molecular level, we designed 3D-structures of characteristic stretches of CS10. CS10 fragments with clustered sulfate groups showed complex patterns of hydrophobic and hydrophilic patches most likely suitable for interactions with protein binding partners. The significance of CS10 interactions with the complement system as well as its anti-malarial effect for prospective drug application are discussed.
Gesehen am 21.06.2021